Synchronous transnational collaborative learning: An interesting model of education to learn medicine in global perspectives (South East Asia Journal of Public Health, 2013)
There is a significant gap between teaching and use of interesting technological resources by most of the faculties in medical schools around the globe. The objective of this paper is to highlight a Malaysian medical schools experience on the use of a Synchronous Transnational Collaborative Learning (STCL) methodology using MedEdWorld a technological resource of medical education, based at Dundee University, UK. A cross sectional study was carried out on 11 year-4 students and one facilitator of University Kebangsaan Malaysia (UKM) Medical Centre who participated in MedEdWorlds STCL topic Yellow Newborn Infant: Normal or abnormal, that is the question held on 24 March 2010 at 0800 hrs GMT. Other participating institutions were from Romania, Finland, Taiwan and Great Britain. The topic was delivered by a consultant from Dundee University, which lasted for one hour. At the end of the STCL presentation, a questionnaire was administered to all of the UKM Medical Centres participants to investigate their experience. The participants experiences were very positive and they loved it. The STCL was an interesting way to learn medicine in global perspectives, live and in the virtual presence of those from other international institutions. Medical schools should be promising to adopt STCL in order to promote medical education in an interesting way. This paper offers other medical schools, especially of the South East Asian Region, a window to promote further development of medical education and practice. DOI: http://dx.doi.org/10.3329/seajph.v1i1.13222 South East Asia Journal of Public Health 2011:1:59-63